Application of the Concepts of Pedagogical Innovation in the Formation of the Student's Personality in the Educational Process and Their Importance - Dilnaz Dauletnazarova Baxitovna; Radjapova Lobar Madyorovna (International Journal on Integrated Education, 2021)
Teaching scientists about ideas, innovation. Described in the article about the importance of innovation in education system. Information about the typs of educational innovation and its importance.